MODEL PEMBELAJARAN KOOPERATIF THINK-TALK-WRITE (TTW) DAN SOFTWARE AUTOGRAPH DALAM MEMPERSIAPKAN PENDIDIK MATEMATIKA MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Simanjuntak, Maslina (Jurnal Dinamika Pendidikan, 2016)
ABSTRACTThe background of this paper is the lack of readiness of educators in Indonesia, especially for mathematics educators in the ASEAN Economic Community (AEC). The purpose of this paper is to prepare mathematics educators to encounter AEC so that they can compete, and make the AEC as an opportunity, not as a threat to his career. To overcome these problems, the solutions offered are: 1) The mastery in innovative learning model, as an example of cooperative learning model Think-Talk-Write (TTW), which can improve studentsâ mathematics learning outcomes, and the ability of students mathematical representation and communication, 2) The mastery of the use of technology, one of them is using mathematical software called Autograph, which can make mathematics educators have the creativity in showing the beauty of mathematics so that can attract the learners to learn. The mastery of an innovative learning model and the mastery of the use of technology such as Think-Talk-Write (TTW) and Autograph is expected to be the solution to improve the quality of mathematics educators in Indonesia.Keywords: Think Talk Write (TTW), AutographABSTRAKLatar belakang penulisan makalah ini adalah masih rendahnya kesiapan para pendidik di Indonesia khususnya pendidik matematika dalam menghadapi Masyarakat Ekonomi ASEAN (MEA). Tujuan penulisan makalah ini adalah untuk mempersiapakan para pendidik matematika dalam menghadapi MEA sehingga dapat bersaing, dan menjadikan MEA sebagai peluang bukan ancaman bagi kariernya. Untuk mengatasi permasalahan tersebut maka solusi yang ditawarkan adalah: 1) Penguasaan model pembelajaran yang dapat inovatif, sebagai contoh model pembelajaran kooperatif tipe Think-Talk-Write (TTW) yang dapat meningkatkan hasil belajar matematika siswa, dan kemampuan representasi serta komunikasi matematis siswa, 2) Pengguasaan terhadap penggunaan tekhnologi salah satunya penggunaan software matematika yaitu Autograph yang dapat membuat pendidik matematika memiliki kreativitas dalam memperlihatkan keindahan dari matematika yang dapat menarik minat peserta didik untuk belajar. Pengguasaan model pembelajaran yang inovatif, dan pengguasaan penggunaan tekhnologi seperti Think-Talk-Write (TTW) dan Autograph diharapkan dapat menjadi solusi untuk meningkatkan mutu pendidik matematika di Indonesia.Kata kunci: Think Talk Write (TTW), Autograph.